Sarcocystis and Hepatozoon Infections in Tongues of Bobcats (Lynx rufus) in Oklahoma, USA - Jitender P. Dubey; Aditya Gupta; Benjamin M. Rosenthal; Mason Reichard (Parasitologia)
Archived, frozen tongues of 56 bobcats (Lynx rufus) from Oklahoma, USA, were tested for parasites. Testing for Sarcocystis infections included microscopic examination of unstained muscle squashes, histological sections of paraffin-embedded tissues, and molecular characterization. By a combination of both compression methods and histology, sarcocysts were found in 28 (50.0%) of 56 bobcats. In compression preparations, the sarcocyst wall appeared thin and protrusions were not clear. Histologically, tissues were degraded and, in most tongues, only a few sarcocysts were found, except bobcat #35. Multilocus genotyping utilizing 18S rRNA, 28S rRNA, and cox1 genes yielded sequences exhibiting 98–100% identity with both Sarcocystis arctica and Sarcocystis caninum isolates available in the NCBI database. Hepatozoon rufi-like meronts were found in two tongues and is the first report of Hepatozoon infections in bobcats in Oklahoma.